The Impact of Non-Arabic Media Broadcasting in Arabic on the Arab Audience: News Coverage on the Russian-Ukrainian War in Al-Hurrah and Russia Today Channels: A Case of study from 2022 to 2023 - Hasan, Mohammad (Eximia, 2023)
Non-Arabic media broadcasting in Arabic has become increasingly prevalent in the Arab world, offering an alternative perspective to the predominantly Western-oriented media outlets in the region. This article examines the impact of non-Arabic media broadcasting in Arabic on the Arab audience's perception of the Russian-Ukrainian war, focusing on the news coverage provided by Al-Hurrah and Russia Today channels from February 2022 to February 2023. The article explores how the news coverage of these channels shapes the Arab audience's understanding of the conflict, and how it contributes to shaping the overall narrative and discourse around the issue. The article draws on qualitative data from interviews and focus groups with Arab viewers, as well as content analysis of the news coverage provided by the two channels. The findings of the article provide insights into the complex and varied impact of non-Arabic media broadcasting in Arabic on the Arab audience, highlighting the importance of considering the audience's pre-existing attitudes and beliefs, the quality and accuracy of the news coverage, and the broader political and social context in which the news is received.